2011
DOI: 10.1111/j.1471-0528.2011.03133.x
|View full text |Cite|
|
Sign up to set email alerts
|

Decline in βhCG levels between days 0 and 4 after a single dose of methotrexate for ectopic pregnancy predicts treatment success: a retrospective cohort study

Abstract: In current protocols for the medical management of ectopic pregnancies, the first indication of treatment response is obtained no sooner than day 7. We examined whether human chorionic gonadotrophin (bhCG) trends between days 0 and 4 after methotrexate provide an earlier indication of the likely outcome. Of 33 patients where serum bhCG dropped between days 0 and 4 after methotrexate, the ectopic pregnancy was resolved in 88% of cases without further treatment. Of 12 women where serum bhCG rose between days 0 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
2
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 5 publications
7
42
2
5
Order By: Relevance
“…The overall success rate of methotrexate treatment in this study was 76.3%, which is essentially in accordance with that reported by the two previous reports (11,12). In the present study, a 63.4% probability of treatment success was found to be related to a rise in serum β-hCG values between days 0 and 4, which is similar to that indicated by Nguyen et al (11).…”
Section: Discussionsupporting
confidence: 82%
“…The overall success rate of methotrexate treatment in this study was 76.3%, which is essentially in accordance with that reported by the two previous reports (11,12). In the present study, a 63.4% probability of treatment success was found to be related to a rise in serum β-hCG values between days 0 and 4, which is similar to that indicated by Nguyen et al (11).…”
Section: Discussionsupporting
confidence: 82%
“…The treatment success rate in our study (75%) was similar to the success rates reported in 2010 by Nguyen et al (76%) [9], and by Skubiz et al (77%) [10]. However, in the study by Nguyen et al, the predictive value of the β-hCG level decrease between days 0 and 4 for treatment success was very high.…”
Section: Discussioncontrasting
confidence: 48%
“…In their study, the success rate of single-dose MTX treatment in all patients in whom β-hCG levels decreased between days 0 and 4 (12 patients) was 100%, and they concluded that follow-up until day 7 may not be required in these patients [9]. Skubitz et al, stated that β-hCG levels decreased between days 0 and 4 in 29 out of 33 patients who were successfully treated with a single dose of MTX (88% success rate), and this is a clinical indicator for predicting the success of single-dose MTX treatment, with the likelihood of 88% [10].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The failure of medical therapy was defined as requirement of surgical therapy after methotrexate was begun. The initial β-hCG value of <1000 mIU/ml did not have any failure, in the failure group the mean level of β-hCG was 5086 mIU/ml as compared to success group which was 3495 mIU/ml.…”
Section: Discussionmentioning
confidence: 99%